(untitled) (Scientific journal of the Fergana State University, 2023)
Health is a natural, absolute and enduring life value that occupies the top rung on the hierarchical ladder of values, as well as in the system of such categories of human existence as interests and ideals, harmony, beauty, meaning and happiness of life, creative work, program and rhythm of life.